2020
DOI: 10.1016/j.nicl.2020.102439
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectome fingerprint of sleep quality in insomnia patients: Individualized out-of-sample prediction using machine learning

Abstract: Highlight Short-term and chronic insomnia are two subtypes of insomnia. Functional connectome predicts individual sleep quality for both two subtypes. Shared and distinct neural basis underlying poor sleep quality between two subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Studies have also used MRI signals for the identification of insomnia (Li et al 2019, Dai et al 2020, Ma et al 2020. Out of all these studies, Monroe (1967) have the biggest data set containing 96 patients out of which 48are insomniacs and 48 are used as control subjects.…”
Section: Detailed Analysis Of Insomnia Detection Using MLmentioning
confidence: 99%
“…Studies have also used MRI signals for the identification of insomnia (Li et al 2019, Dai et al 2020, Ma et al 2020. Out of all these studies, Monroe (1967) have the biggest data set containing 96 patients out of which 48are insomniacs and 48 are used as control subjects.…”
Section: Detailed Analysis Of Insomnia Detection Using MLmentioning
confidence: 99%
“…Shahid et al ( 22 ) employed CNN segmentation of the pharynx of patients with OSA by analyzing the self-produced MRI data of 50 participants, and the Jaccard coefficient for the pharynx being segmented was approximately 86%. Ma et al ( 23 ) employed the multivariate relevance vector regression method to detect short-term/acute and chronic subtypes by analyzing self-produced MRI data of 73 participants. They found that FC predicted sleep quality in both short-term/acute and chronic insomnia and that FC patterns changed during the transition from short-term/acute to chronic insomnia.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals who smoke are at greater risk of experiencing deficient sleep ( Brook et al, 2015 ; Cohrs et al, 2014 ; Kashyap et al, 2001 ), depression, anxiety, fatigue, and concentration difficulties ( Hahad et al, 2022 ; Patten et al, 2000 ). Numerous studies have investigated the neural correlates of deficient sleep ( Bai et al, 2022 ; Fjell et al, 2021 ; Liu et al, 2019 ; Ma et al, 2020 ). For instance, poorer sleep quality was related to faster thinning of the right lateral temporal cortex in a longitudinal study of aging ( Fjell et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%